"La falta de citacion a los demandados por pensiones alimenticias y su incidencia en la acumulación de las pensiones" - Chumaña Vinueza, Manuel Humberto (2015)
CHAPTER I. In this chapter, we find the introduction, which is nothing more than a summary of this research, analyzing where the problem and all the parts that generate the same born, objectives, assumptions and variables that arise within this legal research. CHAPTER II The second chapter provides the background to the research, development framework, case law, legislative framework and comparative law CHAPTER III contains field research in the areas of research solved by applying photo-solving techniques, such as survey and interview. CHAPTER IV Performs analysis and interpretation of results in relation to the research hypothesis. CHAPTER V. In this chapter we have the conclusions and recommendations, where problems are identified and solutions to the issue under investigation is given. CHAPTER VI Here we find the proposal for a legal solution to the problem treated.